Substitution between Real and Accruals-Based Earnings Management after Voluntary Adoption of Compensation Clawback Provisions - Chan, Lilian H.; Chen, Kevin C. W.; Chen, Tai Yuan; Yu, Yangxin (The Accounting Review, 2015)
To deter financial misstatements, many companies have recently adopted compensation recovery policies—commonly known as ‘‘clawbacks’’—that authorize the board to recoup compensation paid to executives based on misstated financial reports. Clawbacks have been shown to reduce financial misstatements and increase investors’ confidence on earnings information. We show that the benefits come with an unintended consequence of certain firms substituting for accruals management with real transactions management (e.g., reduce research and development [R&D] expenditures), especially firms with strong incentives to achieve short-term earnings targets, such as firms with high growth or high transient institutional ownership. As such, the total amount of earnings management does not decrease subsequent to clawback adoption. We further show that although real transactions management temporarily boosts those clawback adopters’ short-term profitability and stock performance, this trend reverses after three years. In summary, clawbacks may have unexpected effects for a subset of firms whose managers are under greater pressure to meet earnings goals.